LITERARY PROCESS OF THE END OF XIX - EARLY XX CENT. IN THE CRITICAL SKETCHES AND MEMOIRS OF KH. A. ALCHEVSKA - Malanii O. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the critical sketches and essays, memoirs, memories with “remarks”, autobiography of Khrystia Alchevska-Jr., her thoughts and views on the literary process in Europe and Ukraine at the turn of the 19th and 20th centuries. The author lays emphasis on the names and public figures who shaped Kh. Alchevska as a creative personality, crystallized her talent of a writer and formed her civic position.